Zametki o stile kak gumanističeskoj strukture teksta: (k 70-letij professora S. Gajdy) - Mišlanov, Valerij A.; Salimovskij, Vladimir A. (Stylistyka, 2020)
The paper analyzes a notion of style developed by S. Gajda as a humanistic structure of a text. The characteristics of a scientist’s notion with presumably wide (for stylistics) subject area – implementation of personal author and social cultural manifestations of text activity in different versions of comprehensive organisation of a verbal product – and stylistics categories with huge potential for synthesis are given. The sources of a style as a higher organizational body for a text in the works of the representatives of aesthetic realism school, Russian and Czech scientists are looked at. The fruitfulness of the introduction of human activity understandings into the integrated research of style is justified.